Mitigating Corrosion in Downhole Environments of Oil and Gas Operations: Mechanisms, Challenges, and Control Strategies - Ahmed, Ezz; Liu, Jianguo; Liu, Jing (Trends in Sciences, 2025)
As oil and gas exploration and production extend into deeper and more challenging environments, the prevalence of acid gases in high-temperature, high-pressure conditions intensifies corrosion risks. This review examines corrosion mechanisms in downhole environments, focusing on the impact of CO2, H2S, and O2, as well as key forms of degradation, including pitting, crevice, under-deposit, stress corrosion cracking, and erosion-corrosion. Corrosion control strategies such as inhibitors, surface coatings, and material selection are analyzed, highlighting their effectiveness and limitations. Additionally, the role of advanced dissolvable tools in enhancing operational efficiency and reducing post-fracture cleanup, their controlled corrosion mechanism, and application case studies are discussed. Despite significant progress, gaps remain in understanding gas interactions, corrosion behavior in extreme conditions, and the long-term performance of mitigation strategies. Future research should focus on refining corrosion prediction models, optimizing material performance, and evaluating economic feasibility, development, and practical use of advanced technologies to ensure reliable and cost-effective downhole operations. HIGHLIGHTS Comprehensive analysis of corrosive gases, exploring the distinct roles of CO2, H2S, and O2 in influencing corrosion mechanisms in downhole environments, with an emphasis on the impact of environmental factors on alloy corrosion. Detailed examination of pitting, crevice, under-deposit, stress corrosion cracking, and erosion-corrosion as they pertain to oilfield conditions. Corrosion control techniques and their effectiveness in mitigating corrosion through corrosion inhibition, surface coatings, and materials selection for managing corrosion in complex downhole scenarios Advanced dissolvable tools, a desired type of corrosion in downhole wells, demonstrating how they improve well efficiency by eliminating milling, reducing downtime, and lowering intervention costs. Additionally, discussing their corrosion mechanism, and economic benefits, as well as providing case studies. A summary of a wide range of corrosion data of different types of alloys under downhole settings. Suggested future research direction in eco-friendly inhibitors, smart coatings, optimized alloys, and AI-driven predictive model to enhance reliability, sustainability, and cost-effectiveness in downhole environments. GRAPHICAL ABSTRACT